Experimental rig for dynamical analysis of a floating body; Penggassan biomass (ujikaji injin disel) = gasification of biomass; Suatu kajian keatas sinaran surai : pengukuran dan analisis; Penggasan biomass; Lighting control in building automation; Portable air-cond unit; Group technology : grouping and tooling analysis in a machine shop; Penganalisaan sistem pengagihan gas dengan bantuan komputer [mikrofilem] - Wong, Wai Keong; Razuki Ibrahim; Rahmat Mohsin; Yeoh, Lean Inn; Ismail Salleh; Mohd. Asngari Saion; Lai, Fook Nyan; Mohd. Ariff Roslan (Kuala Lumpur : UTM, 1988)
Thesis (Bachelor of Mechanical Engineering (Marine Technology)) Universiti Teknologi Malaysia, 1988